Patterns of pregabalin initiation and discontinuation after its subsidy in Australia. Issue 9 (22nd March 2020) - Chiu, Tricia; Brett, Jonathan; Pearson, Sallie‐Anne; Schaffer, Andrea L.
Abstract : Following the 2013 public subsidy of pregabalin in Australia for neuropathic pain not responding to other medicines, use and misuse increased substantially. We used pharmaceutical dispensing claims for a 10% sample of Australians to quantify initiation, discontinuation and dispensing of other analgesics before and after initiation. We identified 130 770 people initiating pregabalin between 2013/14 and 2017/18 (median age: 61 years; 56.8% female). Discontinuation rates at 1‐year increased from 77.0% in 2013/14 to 85.9% in 2017/18; 38% only had 1 dispensing. Approximately 1/3 (37.5%) initiated on the lowest strength capsule (25 mg) with only 31.2% later up‐titrating to a higher strength. 47.4% and 53.0% were dispensed opioids within 180 days before and after pregabalin initiation, respectively. Many individuals are using pregabalin for short treatment durations and low dose ranges not consistent with treatment of neuropathic pain, which is generally a chronic condition. This may suggest poorer tolerability than observed in clinical trials, or use for other conditions, some of which may be for indications where the balance of benefits and risk is less clear.